Repetitions - Abbott, Scott (punctum books, 2013)
In 1994, after following a character in Peter Handke's novel Repetition into what is now Slovenia and after traveling in landscapes of Handke's youth, Žarko Radaković and Scott Abbott published a two-headed text in Belgrade, Ponavljane, now published in English by punctum as Repetitions. The possibility of narration in two voices, complicated by the third voice that is Peter Handke's own narrator, is the main focus of deliberation while traveling and reading and writing. Repetitions begins with Abbott's text, a fairly straightforward travel narrative. It ends with Radaković's account of the same events, much less straightforward, more repetitious, more adventuresome. Two aspects make the double-book unique. First, it represents experiences shared by two authors whose native languages are Serbian and English respectively (German is their only common language). The authors' perspectives contrast with and supplement one another: Radaković grew up in Tito's Yugoslavia and Abbott comes from the Mormon American West; Radaković is the translator of most of Peter Handke's works into Serbo-Croatian and Abbott translated Handke's provocative A Journey to the Rivers: Justice for Serbia for Viking Press and his play Voyage by Dugout: The Play of the Film of the War for PAJ (Performing Arts Journal); Radaković was a journalist for Deutsche Welle in Cologne and Abbott is a professor of German literature at Utah Valley University; Radaković is the author of several novels and Abbott has published mostly literary-critical work; and so on. Two sets of eyes. Two pens. Two visions of the world.